Menata Ulang Relasi Majelis Permusyawaratan Rakyat dan Presiden Melalui Politik Hukum Haluan Negara - Sutan Sorik; Dian Aulia (The Constitutional Court of the Republic of Indonesia, 2020)
This study discusses the relationship between the MPR and the President in the formation, establishment and accountability of achieving national development. The research method used in this study is qualitative, with normative juridical type of research. The results of the study indicate that post-national development reform is not based on concrete guidelines as outlined in the State Policy. Development is carried out by the President and Vice President elected by referring to the vision and mission at the time of nominating the presidential and vice presidential elections. So that national development often experiences political conflicts that cause unsustainable national development, it is also due to the absence of state institutions that are able to fully control the achievement of national development plans and their accountability. Therefore, the arrangement of relations between the MPR and the President should have been carried out. Ideally, it is expected that the MPR and the President will work together in making and setting the country’s direction. The MPR and the President must coordinate with the principle of checks and balances. So that the goal of forming an Indonesian government listed in the fourth paragraph of the opening of the 1945 Constitution can be achieved.